BIMBINGAN TEKNIS PENGEMBANGAN WEB DI SMKN 2 MAGELANG GUNA MENDUKUNG MEDIA INFORMASI KEGIATAN SEKOLAH - Uning Lestari; Joko Triyono; Erfanti Fatkhiyah (LP3K Lampung, 2020)
Currently the use of website technology has become a necessity and has been applied in many fields such as economy, public services, education, socio-politics, health, lifestyle, health, government, trade and so on. The website is used for business purposes, information delivery, transaction processing and data processing. As important as the use of websites is, in the education sector, a website is also needed as a means of supporting the teaching and learning process, promotion and information media to users. SMK N 2 Magelang in an effort to improve web creation and management skills for teachers and administrative staff, has organized web development training and technical guidance. This activity is in collaboration with the Department of Informatics, IST AKPRIND Yogyakarta as a resource for training activities on website development with the CMS Website (Content Management System). This activity got satisfactory results because the teachers managed to create a website / blog to support improving the quality of student learning. Administrative staff also gain knowledge of good web management and successfully create additional features and content that are added to the school website. With these results, it is expected to increase the credibility of SMKN 2 Magelang